2021
DOI: 10.1097/gox.0000000000003431
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Lymphatic Reconstruction: Technical Points and Literature Review

Abstract: Summary: Recent studies have provided evidence that lymphovenous bypass—microsurgical re-routing of divided lymphatics to an adjacent vein—performed at the time of lymph node dissection decreases the rate of lymphedema development. Immediate lymphatic reconstruction in this setting is technically demanding, and there is a paucity of literature describing the details of the surgical procedure. In this report, we review the literature supporting immediate lymphatic reconstruction and provide technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 25 publications
0
50
0
1
Order By: Relevance
“…[4][5][6] Therefore, many surgeons began describing this procedure as an immediate lymphatic reconstruction (ILR), rather than preventive or prophylactic. [7][8][9] Boccardo and colleagues' results have been replicated by several retrospective and prospective studies. A 2018 meta-analysis of 4 papers found that patients who underwent upper-or lower-extremity ILR had a relative risk of 0.33 for developing lymphedema when compared to controls (P<0.0001).…”
Section: Classic and Modified Techniques Of Immediate Lymphatic Reconstructionmentioning
confidence: 78%
See 1 more Smart Citation
“…[4][5][6] Therefore, many surgeons began describing this procedure as an immediate lymphatic reconstruction (ILR), rather than preventive or prophylactic. [7][8][9] Boccardo and colleagues' results have been replicated by several retrospective and prospective studies. A 2018 meta-analysis of 4 papers found that patients who underwent upper-or lower-extremity ILR had a relative risk of 0.33 for developing lymphedema when compared to controls (P<0.0001).…”
Section: Classic and Modified Techniques Of Immediate Lymphatic Reconstructionmentioning
confidence: 78%
“…[4][5][6] Therefore, immediate lymphatic reconstruction (ILR) has been adopted by some as an alternative name. [7][8][9] While preliminary results are favorable, concerns exist surrounding scheduling issues, unfavorable proximal lymphovenous pressure gradients, oncologic safety, and anastomotic injury from postoperative radiation. 10 Delayed, distally-based LVA (DD-LVA) is an emerging alternative method that allows surgeons to avoid these issues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, technique may be inconsistent among examiners. 9 In comparison, indocyanine green lymphangiography may be completed by the surgeon in the clinic and is a useful tool with which we can evaluate lymphatic patency. Patients who develop early, persistently increased LDEX scores or clinical lymphedema despite ILR may be appropriate candidates for further workup including ICG evaluation before initiating additional therapy.…”
Section: Future Directionsmentioning
confidence: 99%
“…Attention is paid to identifying and preserving lymphatic channels draining the arm with as much length as possible. It is also critical to preserve axillary vein branches with a suitable length (6-7 cm) found within level one and level two of the axilla, specifically targeting the thoracoepigastric vein, lateral thoracic vein, medial pectoral vein, and branches emanating from the thoracodorsal vein, if possible, from an oncologic perspective (104). If neither of these veins have been preserved, an unnamed vein could be used if it is found within proximity to the lymphatic vessel or alternatively a vein graft could be used.…”
Section: Lymphatic Reconstruction Proceduresmentioning
confidence: 99%